Evaluation of the Determinants of Religious Tourism Development in the Roztocze Region - Małgorzata Flaga; Marek Markiewicz (Barometr Regionalny)
Roztocze possesses considerable cultural assets, conducive to developing tourism. Among them all, the sacred ones are especially significant because they are traces and witnesses of the former multicultural and multireligious character of the region. They are also excellent premises for advancing religious tourism. But there are some barriers that confine opportunities to develop that kind of tourist movement in Roztocze. First of all, is the general weak state of the tourism infrastructure. Besides that, there is an evident lack of professional promotion and elaborated offering of products of religious tourism. It seems that this form of tourism is not emphasized strongly enough in regional and local development strategies.